2001
DOI: 10.1067/mtc.2001.113751
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge after coronary artery bypass graft surgery: Are patients really going home earlier?

Abstract: Early extubation and fast track protocols have resulted in earlier discharge from acute care facilities. However, the anticipated earlier return to home has been offset by the increased use of outpatient nursing services, discharges to extended care facilities, and hospital readmissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 17 publications
0
34
0
3
Order By: Relevance
“…Knowing these correlations can be effective in reducing the length of ICU stay (4). Some measures such as early tracheal extubation can reduce the length of stay in ICU (5); however, there will be some concern that earlier discharge might increase the probability of readmission in ICU (6). Readmission in ICU is usually accompanied with increased hospital mortality and might have poor outcomes (4).…”
Section: Introductionmentioning
confidence: 99%
“…Knowing these correlations can be effective in reducing the length of ICU stay (4). Some measures such as early tracheal extubation can reduce the length of stay in ICU (5); however, there will be some concern that earlier discharge might increase the probability of readmission in ICU (6). Readmission in ICU is usually accompanied with increased hospital mortality and might have poor outcomes (4).…”
Section: Introductionmentioning
confidence: 99%
“…22 Lazar and colleagues found that a significantly higher percentage of CABG cases were discharged to extended care facilities in 1998 compared to 1990 (43.3% versus 2.9%). 23 Their study, although important in highlighting discharge disposition, was limited to 786 patients in a single center in an urban setting. Hannan et al reported that discharge to a skilled nursing facility or rehabilitation hospital was significantly associated with hospital readmission within 30 days of the index CABG procedure.…”
Section: Increase In Nonroutine Dischargesmentioning
confidence: 99%
“…In Zeiten stetig steigender Kosten im Gesundheitswesen und einer Verknappung von Ressourcen, insbesondere im Bereich der intensivmedizinischen Kapazitäten, rücken ökonomische Aspekte eines operativen Verfahrens zunehmend in den Mittelpunkt des Interesses. Obwohl der klinische Nutzen der "Fast-track-" und sogar "Ultra-fast-track-Regime" in der Kardiochirurgie mit der Extubation auf dem OP-Tisch nach wie vor umstritten ist [39,49], existieren erste Fallberichte von Patienten, bei denen ein herzchirurgischer Eingriff in ACAB-Technik als "day case surgery" durchgeführt wurde. Inwieweit sich jedoch die Ergebnisse der Untersuchung von Karagoz et al aus dem türkischen Ankara auf das deutsche Gesundheitswesen übertragen lassen, bleibt zweifelhaft.…”
Section: "Pros Und Cons"unclassified